Guidebook for genetic resources documentation: A self-teaching approach to the understanding, analysis and development of genetic resources documentation - Painting, Kevin A.; Perry, M.C.; Denning, R.A.; Ayad, W.G.; International Plant Genetic Resources Institute (1993)
This guidebook comes with Genebank Management System Software User's Guide, a tutorial and reference guide for use with the Genebank Management System Software (GMS). This guidebook will assist users in making their own decision on the analysis, design, implementation and use of both manual and microcomputer-based documentation systems. (Chinese, Spanish and French versions available)